2016
DOI: 10.1007/s00360-016-1044-7
|View full text |Cite
|
Sign up to set email alerts
|

Di- and tripeptide transport in vertebrates: the contribution of teleost fish models

Abstract: Solute Carrier 15 (SLC15) family, alias H-coupled oligopeptide cotransporter family, is a group of membrane transporters known for their role in the cellular uptake of di- and tripeptides (di/tripeptides) and peptide-like molecules. Of its members, SLC15A1 (PEPT1) chiefly mediates intestinal absorption of luminal di/tripeptides from dietary protein digestion, while SLC15A2 (PEPT2) mainly allows renal tubular reabsorption of di/tripeptides from ultrafiltration, SLC15A3 (PHT2) and SLC15A4 (PHT1) possibly interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 536 publications
1
53
0
Order By: Relevance
“…The present study also provided the evidence of free, dipeptide or tripeptide diets on the regulatory mechanisms in AA absorption and utilization. Generally, free AA, dipeptide or tripeptides hydrolysed from dietary proteins are absorbed in the animal intestinal tract by AA and peptide transport proteins (Bröer, ; Verri et al, ). PepT1 is a member of the proton oligopeptide cotransporter family, transporting all potential 400 dipeptides and 8,000 tripeptides (Daniel & Kottra, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The present study also provided the evidence of free, dipeptide or tripeptide diets on the regulatory mechanisms in AA absorption and utilization. Generally, free AA, dipeptide or tripeptides hydrolysed from dietary proteins are absorbed in the animal intestinal tract by AA and peptide transport proteins (Bröer, ; Verri et al, ). PepT1 is a member of the proton oligopeptide cotransporter family, transporting all potential 400 dipeptides and 8,000 tripeptides (Daniel & Kottra, ).…”
Section: Discussionmentioning
confidence: 98%
“…However, these studies showed that the effects of dipeptides and crystalline amino acids on the growth were controversial in different fish species. In addition, for teleost fish, dietary proteins are broken down to free amino acids, dipeptide or tripeptides forms in intestinal lumen, which is further taken up by amino acid transporters or peptide transporters (Bröer, ; Verri et al, ). Then, these absorbed amino acids are usually transported into tissues including muscle for the synthesis of proteins by blood (Robinson, Yanke, Mirza, & Ballantyne, ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study a 42% reduction in dipeptide transport was observed, similar to that noted for other dipeptides in mammalian systems, where inhibition in the range of 35%–65% has been observed in low sodium experiments (Ganapathy & Leibach, ). The apparent sodium contribution to transport has been attributed to interplay between NHE and peptide transporters ( e.g ., PepT), yet the exact mechanism by which this occurs is unknown (Ganapathy & Leibach, ; Thwaites et al ., ; Verri et al ., ). Pharmacological inhibition of NHE ( e.g ., with amiloride) would help to delineate the role of NHE in hagfish dipeptide acquisition; however, the highly saline nature of both seawater and hagfish plasma precludes such an experiment owing to the reduced solubility of amiloride at elevated salinities.…”
Section: Discussionmentioning
confidence: 97%
“…Pacific hagfish demonstrate an increase in dipeptide transport following a meal, similar to other vertebrates (Figure ; Verri et al ., ) and indicative of a specific and regulated transport pathway. The magnitude of this response ( J max fasted rate: approximately 100 nmol cm −2 h −1 ; fed rate: approximately 200 nmol cm −2 h −1 ) is similar to that reported in other studies (two‐fold; Adibi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a suitable diet nitrogen composition in term of protein, amino acids, digestible protein/ digestible energy ratio, may be crucial to maintain an appropriate fish welfare. Although their precise mechanism of action is not yet fully understood (Verri et al 2017), it has been demonstrated that certain peptides may modulate nutrient digestion and absorption, enhance mineral absorption and/or bioavailability (Kitts and Weiler 2003), trigger the immune system against pathogen infection, have antibacterial properties and highly stimulate head kidney leucocytes (Kitts and Weiler 2003;Hartmann and Meisel 2007;Madureira et al 2010).…”
Section: Introductionmentioning
confidence: 99%